1982
DOI: 10.1037/0033-2909.92.3.641
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety and self-presentation: A conceptualization model.

Abstract: This article presents a self-presentation approach to the study of social anxiety that proposes that social anxiety arises when people are motivated to make a preferred impression on real or imagined audiences but doubt they will do so, and thus perceive or imagine unsatisfactory evaluative reactions from subjectively important audiences. We presume that specific situational and dispositional antecedents of social anxiety operate by influencing people's motivation to impress others and their expectations of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

46
860
2
42

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,307 publications
(983 citation statements)
references
References 112 publications
46
860
2
42
Order By: Relevance
“…Study 5 suggested that SC feedback, but not CQ feedback, caused LSEs to abandon a self-protective social orientation and eagerly risk joining a group. Applying Schlenker and Leary's (1982) model of social anxiety to my results, I suggest that LSEs' usual social inhibitions are a consequence of their desire to create the impression that they are socially valuable (i.e., someone high in SCs), combined with their doubts that they can create that impression. By providing LSEs with SC feedback, I increased their confidence that they could create their desired impression, which alleviated anxiety and allowed them to seek the acceptance they desire.…”
Section: The Social Value Of Traits Affects Social Behaviormentioning
confidence: 83%
“…Study 5 suggested that SC feedback, but not CQ feedback, caused LSEs to abandon a self-protective social orientation and eagerly risk joining a group. Applying Schlenker and Leary's (1982) model of social anxiety to my results, I suggest that LSEs' usual social inhibitions are a consequence of their desire to create the impression that they are socially valuable (i.e., someone high in SCs), combined with their doubts that they can create that impression. By providing LSEs with SC feedback, I increased their confidence that they could create their desired impression, which alleviated anxiety and allowed them to seek the acceptance they desire.…”
Section: The Social Value Of Traits Affects Social Behaviormentioning
confidence: 83%
“…Diese relativ höhere Anstrengung kann beim Lösen dieser Probleme aber zu suboptimalen Leistungen führen. Der Theorie der Selbstdarstellung folgend gelingt den Personen beim Lösen einfacher Probleme eine bessere Selbstdarstellung, wohingegen dies beim Lösen schwieriger Probleme nicht der Fall ist (Schlenker und Leary 1982). In solchen Situationen kann es daher auch zu Stress und kognitiven Störungen kommen, was ein problemadäquates Verhalten nicht wahrscheinlich werden lässt.…”
Section: Das Szenario Networked Fire Chiefunclassified
“…Because inappropriate behavior in public situations is also associated with a potentially negative impression evoked in others ("appearing foolish," cf, Efran & Korn, 1969), fear of negative social evaluation appears to be a pervasive fear that distinguishes high and low dispositional shyness. Leary and Schlenker (1981)and Schlenker and Leary (1982) extended this view of dispositional shyness to situational shyness and fear of positive evaluation as well and integrated the study of shyness into the self-presentational approach to social 542 VIDEOTAPE RECONSTRUCTION 543 interaction proposed by Schlenker (1980). According to this self-presentational view, situalional shyness arises in real or imagined social situations in which people are motivated to make a particular impression on others but doubt that they will do so, because they expect unsatisfactory impression-relevant reactions from others.…”
mentioning
confidence: 99%
“…Thus, this approach focuses on anxiety that arises from the prospect or presence of self-presentational problems; the danger feared is an undesired social evaluation. Schlenker and Leary (1982) called this type of anxiety social anxiety and showed that most of the existing research on shyness and anxiety in social situations can be integrated into their self-presentational framework.Their approach can be applied to dispositional shyness as well. Shy people are characterized by a strong motive to impress others in desirable ways, a chronically low expectancy to accomplish this, the tendency to reflect on undesired impressions they might evoke in others, and high fear of an undesired social evaluation by others (be it positive or negative).…”
mentioning
confidence: 99%
See 1 more Smart Citation